Micro- and nanoplastics: A new cardiovascular risk factor?. (January 2023) - Zhu, Xiaoqi; Wang, Chuanxuan; Duan, Xiaoyu; Liang, Boxuan; Genbo Xu, Elvis; Huang, Zhenlie
Graphical abstract: Highlights: The cardiovascular toxicity of MNPs and plausible mechanisms are explored. MNPs can penetrate intestinal or pulmonary barriers and accumulate in the heart. Main cardiac effects are abnormal HR, pericardial edema, and myocardial fibrosis. Main vascular effects include hemolysis, thrombosis, and blood coagulation. MNPs alter the cardiovascular toxicity of other environmental contaminants. Abstract: Exposure to micro- and nanoplastics (MNPs) is inevitable due to their omnipresence in the environment. A growing body of studies has advanced our understanding of the potential toxicity of MNPs but knowledge gaps still exist regarding the adverse effects of MNPs on the cardiovascular system and underlying mechanisms, particularly in humans. Here, we reviewed up-to-date data published in the past 10 years on MNP-driven cardiovascular toxicity and mechanisms. Forty-six articles concerning ADME (absorption, distribution, and aggregation behaviors) and toxicity of MNPs in the circulatory system of animals and human cells were analyzed and summarized. The results showed that MNPs affected cardiac functions and caused toxicity on (micro)vascular sites. Direct cardiac toxicity of MNPs included abnormal heart rate, cardiac function impairment, pericardial edema, and myocardial fibrosis. On (micro)vascular sites, MNPs induced hemolysis, thrombosis, blood coagulation, and vascular endothelial damage. The main mechanisms included oxidative stress, inflammation, apoptosis, pyroptosis, and interaction between MNPs and multiple cellular components. Cardiovascular toxicity was determined by the properties (type, size, surface, and structure) of MNPs, exposure dose and duration, protein presence, the life stage, sex, and species of the tested organisms, as well as the interaction with other environmental contamination. The limited quantitative information on MNPs' ADME and the lack of guidelines for MNP cardiotoxicity testing makes risk assessment on cardiac health impossible. Furthermore, the future directions of cardiovascular research on MNPs are recommended to enable more realistic health risk assessment.